The Role of Public Administration in Indonesia’s Islamic Education Reform - Zuroqi Mubarok; Himsar Silaban; Pandji Sukmana; T. Herry Rachmatsyah (ISEDU : Islamic Education Journal, 2025)
This study examines the evolution and current challenges of Islamic education policy in Indonesia through qualitative document analysis, a PRISMA guided systematic review, and bibliometric mapping. Legal and regulatory texts, including Law No. 20 of 2003 (SISDIKNAS) and Ministry of Religious Affairs reports, were analyzed using the READ framework to trace thematic shifts. The review targeted 2021-2025 peer-reviewed literature on curriculum, financing, governance, and educator professionalism, with screening per PRISMA. Bibliometrics identified influential works and collaboration patterns. Findings show a shift from centralized control to decentralized, locally adaptive policy. Innovations include integrated curricula, sharia-compliant financing, and strengthened teacher development, yet disparities in administrative capacity and resource allocation persist, yielding uneven quality assurance. The study argues that harmonizing national standards with regional contexts, enhancing inter-ministerial coordination, and embedding maqasid al-Shariah principles are pivotal for equity and accountability. Future research should evaluate digital governance and financing models for scalability and sustained impact. Keywords: Islamic education policy, Qualitative document analysis, PRISMA, Bibliometrics, Curriculum